Gendered Segregation in Danish Standing Parliamentary Committees 1990-2015 - Fiig, Christina (My University, 2018)
Denmark was among the first countries to achieve female enfranchisement to the national parliament (1915) and it is a society with a long tradition for gender equality policies and women’s rights. 100 years later, the Danish case gives grounds for reflections on gender balance, on segregation and positions occupied by women in national parliaments. Drawing on insights from literature on gender and politics and on parliamentary committees, the article asks what the gendered distribution of seats and chairs is in the Danish parliament, the Folketing, and what can explain these gendered patterns. To answer these questions, this article investigates the horizontal and vertical gendered segregation of standing parliamentary committees of the Danish parliament 1990-2015 based on an explorative, longitudinal study. The results show that the Danish parliament is characterized by both vertical and horizontal segregation in relation to parliamentary committees. Both categories of segregation are declining over time, but the analysis reveals interesting patterns of change and stability especially for the horizontal segregation. Several committees have an over-representation (social, education and research and health) and under-representation of women (defence, finance and transport). A number of committees are characterized by a share of 30-40% women. This category is especially interesting as it points towards a decline in horizontal representation.
Keywords: Dänemark; Parlament; Politik; Repräsentation; Segregation; ddc:303 Gesellschaftliche Prozesse; ddc:303